(untitled) (Bangladesh Journal of Agricultural Research, 2011)
Eight maize varieties viz. four composites (Mohor, Barnali, Khoibhutta, and BARI Maize-6) and four hybrids (BARI Hybrid Maize-1, BARI Hybrid Maize- 3, BARI Hybrid Maize Top 1 & Pacific 984), were tested for their response to zinc fertilization (0 and 3 kg Zn/ha) at the Regional Agricultural Research Station (RARS), Jessore (AEZ-11, High Ganges River Floodplain) during 2002- 2005. The varieties were not equally responsive to Zn addition. Except BARI Hybrid Maize-3, all other hybrids showed higher response to Zn compared to composite varieties. Among the hybrids, the Pacific 984 had the highest response followed by BARI Hybrid Maize-1 and BARI Hybrid Maize Top 1, the later two showed identical response. Comparing the composite varieties, their response can be ranked as Barnali ≈ Mohor > Khoibhutta > BARI Maize-6. The result suggests that BARI Hybrid Maize-3 and BARI Maize-6 were the most Zn inresponsive (Zn efficient) varieties. Further it appeared that Pacific 984 gave the highest seed yield, 10.46 t/ha due to Zn application. So, the farmers can grow this variety with an application of Zn @ 3 kg/ha in the deficient soil. The results also indicate that the farmers can cultivate BARI Hybrid Maize-3 in the moderately zinc deficient soils with a minimum dose (1 to 2 kg/ha) of Zn fertilization. Keywords: Maize varieties; zinc fertilization. DOI: http://dx.doi.org/10.3329/bjar.v36i3.9272 BJAR 2011; 36(3): 437-447